1986
DOI: 10.1080/02681218680000191
|View full text |Cite
|
Sign up to set email alerts
|

Pathogenesis of vaginal candidiasis: studies with a mutant which has reduced ability to adherein vitro

Abstract: A spontaneous, cerulenin-resistant mutant of Candida albicans (strain 4918-10) was found to adhere less readily to human vaginal mucosal cells in vitro than a wild type C. albicans (strain 4918). In a murine model of vaginal infection, strain 4918-10 was found to be less virulent than wild type C. albicans, i.e., the infection rate caused by 4918-10 was only 31% of that observed with wild type, 4918. A chitin-soluble extract (CSE) prepared from 4918 blocked attachment of yeast cells to human vaginal epithelia… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
20
1

Year Published

1988
1988
2000
2000

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 51 publications
(21 citation statements)
references
References 16 publications
0
20
1
Order By: Relevance
“…Furthermore, codon bias and the promoter and termination signals of the C. albicans EF-la proteins were remarkably similar to those of S. cerevisiae EF-la. Taken together, these results suggest that C. albicans is more closely related to the ascomycete S. cerevisiae than to the zygomycete M. racemosus.Candida albicans is a dimorphic fungal pathogen that acquires virulence and the ability to adhere to host tissues as it undergoes the transition from yeast to mycelial forms (26,27,37,45,61). The phylogenetic relationship of C. albicans to other fungi is uncertain because of the lack of a sexual cycle, resulting in its being placed in the form subdivision Deuteromycotina (Fungi Imperfecti) along with a diverse group of 15,000 other species (48).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, codon bias and the promoter and termination signals of the C. albicans EF-la proteins were remarkably similar to those of S. cerevisiae EF-la. Taken together, these results suggest that C. albicans is more closely related to the ascomycete S. cerevisiae than to the zygomycete M. racemosus.Candida albicans is a dimorphic fungal pathogen that acquires virulence and the ability to adhere to host tissues as it undergoes the transition from yeast to mycelial forms (26,27,37,45,61). The phylogenetic relationship of C. albicans to other fungi is uncertain because of the lack of a sexual cycle, resulting in its being placed in the form subdivision Deuteromycotina (Fungi Imperfecti) along with a diverse group of 15,000 other species (48).…”
mentioning
confidence: 99%
“…Candida albicans is a dimorphic fungal pathogen that acquires virulence and the ability to adhere to host tissues as it undergoes the transition from yeast to mycelial forms (26,27,37,45,61). The phylogenetic relationship of C. albicans to other fungi is uncertain because of the lack of a sexual cycle, resulting in its being placed in the form subdivision Deuteromycotina (Fungi Imperfecti) along with a diverse group of 15,000 other species (48).…”
mentioning
confidence: 99%
“…Thus, our in vitro studies on adhesion, a process considered a marker for virulence, are compatible with these in vivo data. Moreover, Lehrer et al [23] showed with a cerulenine‐resistant C. albicans mutant a correlation between in vitro adhesion ability and in vivo pathogenicity. The mutants, which adhered less in vitro to vaginal cells, were also less pathogenic in a murine experimental vaginitis model.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, our in vitro studies on adhesion, a process considered a marker for virulence, are compatible with these in vivo data. Moreover, Lehrer et al [23] showed with a cerulenine-resistant C. albicans mutant a correlation between in vitro adhesion ability The adhesion values relate to C.A. cells that adhere to 100 BEC.…”
Section: Discussionmentioning
confidence: 99%